Oral lesions in a newborn: Unusual mucosal manifestation of erythema toxicum neonatorum? - Marcondes Macéa, J.; Piquero Casals, J.; Menta Simonsen Nico, M. (European Journal of Pediatric Dermatology, 2002)
We describe a case of a 1-day-old infant presenting with erythema toxicum neonatorum. Simultaneously with the skin eruption, the patient developed aphthoid erosions and small pustules on his lower lip mucosa. Tzanck and potassium hydroxide preparations of these pustules failed to reveal multinucleated cells or microorganisms. Both the skin and the oral lesions resolved spontaneously after 2 days. We believe that the oral lesions may be a previously unreported mucosal manifestation of erythema toxicum neonatorum.